O discurso rodrigueano: efeitos de autoria(s) do teatro ao cinema - Martins, Cássia Peres (2013)
This work has as objects of analysis the plays Boca de Ouro (1959), A Falecida (1953) e Os Sete Gatinhos (1958) written by brazilian playwright Nelson Rodrigues, and their film adaptations. Boca de Ouro (Golden Mouth), adapted in 1962, directed by Nelson Pereira dos Santos; A falecida (The Deceased), directed by Leon Hirszman, adapted in 1965 and finally Os Sete Gatinhos (The Seven Kittens), directed by Neville D'Almeida, with the adaptation in 1980. The theoretical approach that will serve as the basis for these analyzes will be of Discourse Analysis of French orientation as the main component, as well as other theories that can contribute. Fruit of a basic research imprint bibliographic and interpretive, this paper presents reflections on the subject positions, the positions that underlie the author and director, devoting attention to the characters from the materiality of theatrical text, observing how these positions move in filmic materiality. It will be checked, besides this possibility of subject positions, the inclusion or withdrawals dialogues, the preserved senses, removed or added, through elements, that may or may not work as evidence of authorship, that compose the entire film production, such as music, sets, costumes, image formation by moving the camera (first and second plans, focusing, among other things). This reflection is done while considering the materiality of the film is the result of a collective production, headed by a director with different people responsible for photography, set design, assembly and soundtrack, as well as intervention in the creation of characters for each actor. Thus, the analysis results will be presented in a process of re-signification through which passes the Nelson Rodrigues speech when taken to the cinema and, by the fact of re-signify may introduce evidence that copyright and trademarks that materialize as effects.